Digital Citizenship and Multicultural Education in Contemporary Higher Education - M. Neeharika (CV Edujavare Publishing, 2024)
The rapid expansion of digital technologies has transformed higher education by creating new opportunities for learning, communication, and global engagement. Simultaneously, increasing cultural diversity within universities has highlighted the importance of multicultural education and digital citizenship in preparing students for participation in interconnected societies. This study explores the relationship between digital citizenship and multicultural education in contemporary higher education through a systematic literature review. The findings indicate that multicultural education and digital citizenship are mutually reinforcing concepts that contribute to the development of responsible, ethical, inclusive, and culturally aware learners. Multicultural educational practices enhance students’ appreciation of diversity, while digital citizenship promotes responsible online behavior, critical digital literacy, and respectful engagement in virtual environments. The study further reveals that integrating digital citizenship with multicultural education strengthens intercultural communication, global awareness, social inclusion, and civic participation. A conceptual framework is proposed to explain how digital competence and multicultural awareness collectively contribute to inclusive digital engagement. The findings provide valuable implications for educators, policymakers, and higher education institutions seeking to prepare students for active participation in diverse and digitally connected societies.